Protein requirement of finishing barrows and gilts (110 to 230 lbs) - Robert H Hines; B A Koch; David A Nichols; L M Turlington; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1987)
Eighty barrows and 80 gilts were fed diets containing four crude protein levels (16, 15, 14, and 13%) from approximately 115 lb to a market weight of 230-235 lb. Barrows and gilts were fed separately to determine their protein requirements during the finishing period. Performance traits (ADG, ADF, and F/G) of barrows and gilts were not significantly affected by increasing the protein content of the diet from 13 to 16%. However, barrows linearly decreased in fat thickness at the 10th rib as crude protein content in the diet was increased. Also, percent muscle increased linearly with increased protein for barrows, but increased protein in diets fed gilts did not result in an improvement in carcass leanness, loin eye, or percent muscle.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Protein; Finishing barrows